2018
DOI: 10.12659/pjr.899960
|View full text |Cite
|
Sign up to set email alerts
|

Various Imaging Manifestations of Posterior Reversible Encephalopathy Syndrome (PRES) on Magnetic Resonance Imaging (MRI)

Abstract: SummaryBackgroundPosterior reversible encephalopathy syndrome (PRES), also called the acute hypertensive encephalopathy and reversible posterior leukoencephalopathy syndrome (RPLS), is a neurotoxic syndrome of cerebral vasoregulation classically characterized by bilaterally symmetrical parieto-occipital edema. However, the imaging findings are variable and may occur in other locations such as the frontal lobes, thalami, basal ganglia and brainstem. Most commonly, PRES presents with hyperintense signals on T2 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 33 publications
2
26
0
2
Order By: Relevance
“…Raman et al investigated 92 patients with PRES and found that the most commonly affected region was the parietal and occipital lobes. 13 However, it was also specified that frontal lobes, temporal lobes, basal ganglia, cerebellum, brainstem and thalamus could be in- volved. Similarly, Fugate et al who evaluated 120 patients with PRES reported that parietal and occipital lobes were most commonly affected, followed by the frontal lobe, temporal lobe and cerebellum.…”
Section: Discussionmentioning
confidence: 99%
“…Raman et al investigated 92 patients with PRES and found that the most commonly affected region was the parietal and occipital lobes. 13 However, it was also specified that frontal lobes, temporal lobes, basal ganglia, cerebellum, brainstem and thalamus could be in- volved. Similarly, Fugate et al who evaluated 120 patients with PRES reported that parietal and occipital lobes were most commonly affected, followed by the frontal lobe, temporal lobe and cerebellum.…”
Section: Discussionmentioning
confidence: 99%
“…Laboratuvar tetkiklerinde serum kreatinin değeri:1,46 mg/dL (0,8-1,2), üre:70 mg/dL (17-43), albumin:2,1 g/dL (3,5-5,2), tam idrar tetkikinde ise 3+ protein ve 7 eritrosit mevcuttu. Hematolojik değerlendirmede beyaz küre 3400/mm 3 (4.000-10.000), hemoglobin:7,6 g/dL (11)(12)(13)(14)(15)(16)(17)(18), trombosit:120.000/mm 3 (150.000-450.000) idi. rek yetmezliği yapan çeşitli sebeplere sekonder gelişen reversibl semptom ve görüntüleme bulgularıyla karakterizedir.…”
Section: Olgu Sunumuunclassified
“…Örneğin; PRES tanısı almış 92 hastanın incelendiği bir çalışmada, hastaların %57'sinde difüzyon sekanslarda hiperintensite izlenirken, ADC görüntülerde anlamlı sinyal kaybı izlenmediği (psödo-normalizasyon) saptanmıştır. 15 Olgumuzda ise lezyonlar difüzyon sekansta hiperintens ADC sekansta hipointens izlenmiştir, psödo-normalizasyon saptanmamıştır.…”
Section: Olgu Sunumuunclassified
“…17 CNIinduced neurotoxicity in non-MMA organ transplanted patients can present with a variety of symptoms such as confusion, tremor, seizures, cerebral hemorrhage, ischemic stroke, and posterior reversible encephalopathy syndrome (PRES). 15,[18][19][20] In CNI-induced PRES, the brain magnetic resonance imaging (MRI)-scan typically shows bilateral areas of vasogenic edema, which may be located in the cortex and/or subcortical white matter of brain areas; supplied by posterior circulation. However, an atypical distribution pattern is not infrequently observed, for example, involving the basal ganglia and/or the brain stem, 20 with or without atypical imaging findings (contrast enhancement, hemorrhage or restricted diffusion).…”
Section: Introductionmentioning
confidence: 99%
“…15,[18][19][20] In CNI-induced PRES, the brain magnetic resonance imaging (MRI)-scan typically shows bilateral areas of vasogenic edema, which may be located in the cortex and/or subcortical white matter of brain areas; supplied by posterior circulation. However, an atypical distribution pattern is not infrequently observed, for example, involving the basal ganglia and/or the brain stem, 20 with or without atypical imaging findings (contrast enhancement, hemorrhage or restricted diffusion). 18 Recently, two adult MMA patients received combined liver/kidney transplantation in our center.…”
Section: Introductionmentioning
confidence: 99%